PENYULUHAN DAN VAKSINASI NEWCASTLE DISEASE PADA AYAM BURAS DI DESA MARGA KECAMATAN MARGA KABUPATEN TABANAN - Kencana, G.A.Y.; Suartha, I.N.; Apsari, I.A.P.; Kendran, A.A.S; Suardana, I.B.K. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p06, 2018)
The purpose of this community service is to prevent the incidence of Newcastle Disease in domestic poultry in Marga Dauh Puri Village, Marga Subdistrict, Tabanan Regency. Newacastle disease is highly contagious and can cause high mortality in poultry. Kampong chickens has the potential as a transmitter of Newcastle disease because the maintenance system is semi extensive. Banjar Ole is part of the village of Marga Dauh Puri, where there are many kampong chickens kept extensively. The village of Marga Dauh Puri is highly potential for contracting Newcastle disease, as it is a chicken trade traffic route from Penebel to Denpasar. Community service activities carried out on September 24, 2017, covering the ways of raising chickens and preventing Newcastle Disease by vaccination. Noted there are 450 poultry in Banjar Ole, as many as 372 (82.6%) successfully vaccinated. This is due to some kampong chickens not extensively so not all can be vaccinated. The amount is sufficient for vaccination coverage to produce group immunity. In order to proof that the vaccination program is appropriate, ten blood samples were collected and antibody titer was tested prior vaccination (was found to have a mean antibody titer of 22.2 HI units) which means under protective titer (24 HI units).